Integrating Differentiated Learning and Interdisciplinary Approaches in Curriculum Design for Quality Education: A Case Study in Islamic Universities - Rokhimawan, Mohamad Agung; Ichsan, Ichsan; Aulia, Muhammad Ghozil; Rifai, Ikhsan (Ulumuna, 2025)
This study proposes a conceptual model for integrating differentiated learning and interdisciplinary approaches in the Curriculum Development course within the Islamic Religious Education study program. The research methodology includes participatory observation, in-depth interviews with faculty and students, and document analysis. This qualitative study employs a case study design to examine the implementation of differentiated and interdisciplinary learning strategies in curriculum development courses at three State Islamic Universities: UIN Sunan Kalijaga Yogyakarta, UIN Maulana Malik Ibrahim Malang, and UIN Sunan Ampel Surabaya. These institutions were purposefully selected due to their active involvement in the National Association of Islamic Religious Education scholars and their demonstrated commitment to curriculum innovation. Findings indicate that differentiated learning enhances student engagement, motivation, and comprehension by tailoring materials and assignments to individual abilities and interests. However, several challenges were identified, including time constraints, insufficient technology resources, and the need for faculty development to apply these approaches effectively. The study highlights the importance of institutional support, including ongoing faculty training, improved facilities, and adaptable evaluation mechanisms, in optimizing the implementation of differentiated and interdisciplinary learning. In conclusion, this conceptual approach holds significant potential to enhance educational quality, provided it is backed by the appropriate infrastructure and strategies to meet the varied learning needs of students.